(untitled) (Comprehensive Journal of Science, 2025)
The study aims to identify deaf children’s needs for psychological counseling services and to examine differences by gender, academic qualification, and years of experience. A descriptive survey design was used with a sample of 34 teachers at Al-Amal Center for the Deaf and Hard of Hearing in Al-Zawiya (76.5% female). A 25-item questionnaire was developed, validated by experts and internal consistency, with Cronbach’s alpha = 0.777. Findings show high perceived needs for counseling (overall mean = 2.98; SD = 0.037), with broad agreement on counseling’s role in addressing academic delay, fostering humane school relations, developing students’ abilities and interests, and strengthening school–family collaboration. Independent-samples t-tests revealed no significant differences in perceived needs by gender, qualification, or years of experience. The study recommends strengthening counseling programs in schools for the deaf, training staff, activating partnerships with parents, developing specialized counseling tools, and conducting longitudinal evaluations of counseling impacts on achievement and social adjustment.